Targeting lysine specific demethylase 4A (KDM4A) tandem TUDOR domain – A fragment based approach. Issue 10 (1st June 2018) - Upadhyay, Anup K.; Judge, Russell A.; Li, Leiming; Pithawalla, Ron; Simanis, Justin; Bodelle, Pierre M.; Marin, Violeta L.; Henry, Rodger F.; Petros, Andrew M.; Sun, Chaohong
Graphical abstract: Highlights: Identified fragment 1a that competes with H3K4me3 binding in KDM4A TUDOR domain. X-ray structure of KDM4A TUDOR domain in complex with 1a is presented. Specificity of 1a towards TUDOR domains from other proteins is presented. Abstract: The tandem TUDOR domains present in the non-catalytic C-terminal half of the KDM4A, 4B and 4C enzymes play important roles in regulating their chromatin localizations and substrate specificities. They achieve this regulatory role by binding to different tri-methylated lysine residues on histone H3 (H3-K4me3, H3-K23me3) and histone H4 (H4-K20me3) depending upon the specific chromatin environment. In this work, we have used a 2D-NMR based fragment screening approach to identify a novel fragment (1a ), which binds to the KDM4A-TUDOR domain and shows modest competition with H3-K4me3 binding in biochemical as well as in vitro cell based assays. A co-crystal structure of KDM4A TUDOR domain in complex with 1a shows that the fragment binds stereo-specifically to the methyl lysine binding pocket forming a network of strong hydrogen bonds and hydrophobic interactions. We anticipate that the fragment 1a can be further developed into a novel allosteric inhibitor of the KDM4 family of enzymes through targeting their C-terminal tandem TUDOR domain.